Hematuria as the first sign of multiple myeloma. Issue 8 (10th July 2017) - Alves, Mariana; Moreno, Raul; Rodrigues, Fátima; Rodrigues, Anabela; Fonseca, Teresa
Key Clinical Message: Patients with multiple myeloma may present with several signs and symptoms, inclusive of hemorrhagic diathesis. This case emphasizes the need to suspect uncommon etiologies for common signs and to be aware of the atypical effects of paraproteinemia. Abstract : Patients with multiple myeloma may present with several signs and symptoms, inclusive of hemorrhagic diathesis. This case emphasizes the need to suspect uncommon etiologies for common signs and to be aware of the atypical effects of paraproteinemia.